Design calculation of hydrotransport plant for technologies of highly-concentrated pulps storing - Kirichko, S.N. (Геотехнічна механіка, 2015)
It is for the first time when a method of design calculation based on universal dimensionless quantities and analytical linear dependence between hydraulic gradient, initial shear stress, effective suspension viscosity and volumetric flow rate was proposed for systems for storing tailings in the form of highly-concentrated slurry. A distinctive feature of the proposed non-linear dependence between diameter of the pipeline, initial shear stress, effective suspension viscosity and volumetric flow rate is versatility of coefficients, which do not depend on the properties of solid phase and diameter or material of the pipeline. The findings have been resulted in a decision which helps specifying diameter of the trunk hydrotransport complex providing controllable flow of highly-concentrated pulp, in accordance with the Bingam-Shvedov rheological law, in a structured flow regime with taking into account flow pressure characteristics of the intended pumping equipment.